2018
DOI: 10.1371/journal.pone.0190487
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with long acting injectable ART: A qualitative study among PLHIV participating in a Phase II study of cabotegravir + rilpivirine (LATTE-2) in the United States and Spain

Abstract: Challenges with adherence to daily oral antiretroviral therapy (ART) among people living with HIV (PLHIV) have stimulated development of injectable long-acting (LA) regimens. We conducted 39 in-depth interviews with participants and providers in a Phase IIb study (LATTE-2) evaluating an injectable LA regimen in the U.S. and Spain. Interviews exploring participant and provider attitudes and experiences with LA versus oral ART were audiotaped, transcribed and analyzed using thematic content analysis. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
110
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 36 publications
7
110
0
2
Order By: Relevance
“…We did not include studies which address such barriers through use of alternative regimens or formulations. Use of more potent and/or better tolerated ART regimens such as integrase inhibitors, long-acting and injectable regimens [75][76][77] have shown promise among adults and should be examined among adolescents and youth. Other medication-related interventions among adolescents and youth such as weekends off regimens have been shown to be non-inferior [78], and single-tablet regimens have achieved significantly higher VL suppression rates than multi-tablet regimens [79].…”
Section: Discussionmentioning
confidence: 99%
“…We did not include studies which address such barriers through use of alternative regimens or formulations. Use of more potent and/or better tolerated ART regimens such as integrase inhibitors, long-acting and injectable regimens [75][76][77] have shown promise among adults and should be examined among adolescents and youth. Other medication-related interventions among adolescents and youth such as weekends off regimens have been shown to be non-inferior [78], and single-tablet regimens have achieved significantly higher VL suppression rates than multi-tablet regimens [79].…”
Section: Discussionmentioning
confidence: 99%
“…(27) In a study developed in East Africa, the presence of adverse effects negatively influence the antiretroviral therapy (28) and can affect different areas of human beings, ranging from the physical to the psychosocial. (29) Possible changes to improve compliance with HIV treatment identified in this study were supported by an international study, (30) in which individuals undergoing injectable antiretroviral therapy reported better compliance due to the monthly or six-monthly application regimen.…”
Section: Discussionmentioning
confidence: 62%
“…14 In a separate substudy of participants (n ¼ 27) in the LATTE-2 study, qualitative interviews were conducted at sites in both the United States (n ¼ 11) and Spain (n ¼ 16) to explore participants' experiences with cabotegravir LA þ rilpivirine LA. 15 Findings underscored the convenience of LA injectable therapy versus daily oral pills and the emotional benefits such as ameliorating the experience of internalized stigma and the related "daily reminder of HIV." These logistical and psychosocial benefits helped participants live with more flexibility and with less anxiety over daily dosing and the risk of accidental HIV disclosure.…”
Section: Discussionmentioning
confidence: 99%